2012
DOI: 10.1039/c2sc00977c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a robust supramolecular method to prepare well-defined nanofibrils from conjugated molecules

Abstract: In order to produce materials with tailored structures and functions via supramolecular self-assembly of molecular precursors in a predictable fashion, it is necessary to develop 'supramolecular methods' based on structurally simple 'supramolecular synthons'. Thus, the formation of one-dimensional aggregates from p-conjugated molecules requires a combination of non-covalent interactions that efficiently suppresses lateral aggregation, promotes one-dimensional aggregation, and is also compatible with a producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 67 publications
2
63
0
Order By: Relevance
“…In this way, the versatile properties of different types of silk materials are precisely tailored according to their function [11][12][13] . Inspired by this example of nature's design principles, the selective formation of onedimensional nanostructures from b-sheet-forming oligopeptides and oligopeptide-modified polymers has been extensively investigated [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . However, the thermomechanical properties of the corresponding bulk materials have rarely been studied in much detail [29][30][31] .…”
mentioning
confidence: 99%
“…In this way, the versatile properties of different types of silk materials are precisely tailored according to their function [11][12][13] . Inspired by this example of nature's design principles, the selective formation of onedimensional nanostructures from b-sheet-forming oligopeptides and oligopeptide-modified polymers has been extensively investigated [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . However, the thermomechanical properties of the corresponding bulk materials have rarely been studied in much detail [29][30][31] .…”
mentioning
confidence: 99%
“…An amino acid sequence is chosen that will preferentially form β ‐sheets (in this case, parallel β ‐sheets) with stabilizing hydrogen bonds being formed between adjacent chains. The final feature is a terminal end group (green) that further directs nanostructure formation through hydrogen bonding NHAc and oligopeptide motifs as well as π‐stacking Fmoc units . This molecular architecture acts as a “supramolecular synthon” where the individual segments of a single molecule are specifically designed to cooperatively direct the formation of well‐defined nanostructures .…”
Section: Approaches To Isolable Collections Of Single Pda Chainsmentioning
confidence: 99%
“…Previous studies have shown that peptides with as few as four amino acid residues can assemble into fibrous gels that mimic the structure of soft tissues, giving rise to hybrid materials that are viable for in vivo applications . Peptide‐hybrids containing conjugated thiophene or phenylene oligomers have been analyzed and shown to form canonical structures based upon the amino acid sequence of the peptide, resulting in fibrillar structures with unique optical properties . Composites containing peptide assemblies and CPs such as polyacetylene and poly(3,4‐ethylenedioxythiophene) (PEDOT) derivatives have also been reported, but bulk hydrogel structure, mechanical and electrical properties have yet to be investigated in detail.…”
Section: Introductionmentioning
confidence: 99%